Characterization of Helicobacter pylori VacA‐containing vacuoles (VCVs), VacA intracellular trafficking and interference with calcium signalling in T lymphocytes. (16th July 2015) - Kern, Beate; Jain, Utkarsh; Utsch, Ciara; Otto, Andreas; Busch, Benjamin; Jiménez‐Soto, Luisa; Becher, Dörte; Haas, Rainer
Summary: The human pathogen H elicobacter pylori colonizes half of the global population. Residing at the stomach epithelium, it contributes to the development of diseases such as gastritis, duodenal and gastric ulcers, and gastric cancer. A major factor is the secreted vacuolating toxin VacA, which forms anion‐selective channels in the endosome membrane that cause the compartment to swell, but the composition and purpose of the resulting VacA‐containing vacuoles (VCVs) are still unknown. VacA exerts influence on the host immune response in various ways, including inhibition of T‐cell activation and proliferation and suppression of the host immune response. In this study, for the first time the composition of VCVs from T cells was comprehensively analysed to investigate VCV function. VCVs were successfully isolated via immunomagnetic separation, and the purified vacuoles were analysed by mass spectrometry. We detected a set of 122 VCV‐specific proteins implicated among others in immune response, cell death and cellular signalling processes, all of which VacA is known to influence. One of the individual proteins studied further was st romal i nteraction m olecule (STIM1), a calcium sensor residing in the endoplasmic reticulum (ER) that is important in store‐operated calcium entry. Live cell imaging microscopy data demonstrated colocalization of VacA with STIM1 in the ER and indicated that VacA may interfere with the movement of STIM1 towards the plasma membrane‐localized c alcium r elease a ctivated c alcium channel protein ORAI1 in response to Ca 2+ store depletion. Furthermore, VacA inhibited the increase of cytosolic‐free Ca 2+ in the Jurkat E6‐1 T‐cell line and human CD4 + T cells. The presence of VacA in the ER and its trafficking to the Golgi apparatus was confirmed in HeLa cells, identifying these two cellular compartments as novel VacA target structures.